2013
DOI: 10.4012/dmj.2013-069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fiber post length and bone level on the fracture resistance of endodontically treated teeth

Abstract: This study evaluated the combined influence of horizontal bone loss and post length on the fracture resistance of endodontically treated teeth (ETT). Twenty premolars were endodontically treated and divided into four groups of two different post insertion depths (5 and 7 mm) and two alveolar bone levels from cement-enamel junction (2 and 5 mm). After posts (RelyX Fiber Post) were cemented using a self-adhesive resin cement (RelyX Unicem Aplicap) and cores were built up (Filtek Supreme XT Universal Restorative,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Except for Group Z, there was no significant difference in fracture resistance between the short and long posts in the other groups. Similar to other studies, it shows that increasing the length of the post does not provide additional resistance to fracture 40‐44 . In this study, the fracture strength of the LW group was found to be significant only in Group Z compared with the SN group.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Except for Group Z, there was no significant difference in fracture resistance between the short and long posts in the other groups. Similar to other studies, it shows that increasing the length of the post does not provide additional resistance to fracture 40‐44 . In this study, the fracture strength of the LW group was found to be significant only in Group Z compared with the SN group.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to other studies, it shows that increasing the length of the post does not provide additional resistance to fracture. [40][41][42][43][44] In this study, the fracture strength of the LW group was found to be significant only in Group Z compared with the SN group. Although no significant difference was observed in other groups, LW groups showed higher average fracture strength values compared with other dimensions.…”
Section: Ta B L E 2 Means and Standard Deviationsmentioning
confidence: 95%
“…In order to receive the loads, samples were embedded, with the help of a surveyor, parallel to their vertical axis in acrylic blocks (Acropars, Tehran, Iran) 2 mm above the CEJ 232425. Loads were then applied using a universal testing machine (Zwick Roell Group, Ulm, Germany) at a crosshead speed of 0.5 mm/min on the central fossa of each crown, through a 4-mm diameter spherical wedge, at an angle of 45 degrees to the long axis of the roots (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Each instrument was used for five canals up to size X3 (30/0.07) during preparation EDTA cream (SURE-PREP, SURE ENDO, korea) used inside canal to enhance instrumentation and 2ml of distilled water and 2ml of 5.25% sodium hypochlorite (NaOCl) irrigation were used between each file size, there after each canal received a final irrigation of 3 ml EDTA solution to remove the smear layer then 3 ml of NaOCl after washing the EDTA with 2ml of distilled water, then the canals flushed with 10 ml distilled water to remove any remnant of irrigation materials. [12] After drying with paper points the canals were obturated with single cone using size X3 guttapercha cone which was fitted at the working length with slight resistance [tug back] effect, in conjunction with endodontic sealer (AD SEAL) (META BIOMED CO.LTD, Korea).…”
Section: Methodsmentioning
confidence: 99%
“…Then the resin was light-cured with light curing device with 1600mW/mm 2 intensity for 40 seconds (Da-lux, Dia Dent Korea) in the occlusal direction; the intensity of light cure had been checked before using with a radiometer and rechecked after each curing. [12,13] The core build-ups with composite resin which were standardized using the same size of a cellulite core-forming matrices to ensure the uniformity of the specimens. Then all the specimens were maintained in 100% humidity, for 24 hours, at 37°C.…”
Section: Methodsmentioning
confidence: 99%